COVID-19 PANDEMIC: IMPLICATIONS FOR MENTAL HEALTH IN THE POPULATION FROM VALE DO PARANHANA, BRAZIL (Movimenta (ISSN 1984-4298), 2024)
Objective: This study seeks to explore the impact of the COVID-19 pandemic on the psychic and emotional condition of the population of the municipalities of Vale do Paranhana, correlating the findings with the epidemiological bulletins of COVID-19. Method: This is an exploratory research with a cross-sectional design and a quantitative approach, whose data collection took place between May and September 2022, in Vale do Paranhana, Rio Grande do Sul, Brazil. Results: There was no increase in cases of self-harm and suicide in the intrapandemic period, however, it was possible to identify a strong correlation between cases of self-harm, suicide, confirmed cases and deaths from COVID-19. Conclusion: The set of findings obtained in the present study indicate that the COVID-19 pandemic negatively affected the mental health of the population of Vale do Paranhana.
Keywords: COVID-19, Pandemics, Mental Health.